Can angle-resolved x-ray measurements help determine small level splittings in highly charged ions?. (August 2015) - Wut, Z W; Kabachnik, N M; Surzhykov, A; Dong, C Z; Fritzscheh, S
Synopsis: The angular distribution and photon-photon angular correlation have been studied for x-ray emissions from two-step radiative cascades that proceed via two or more overlapping intermediate resonances. From this study, we suggest that accurate angle-resolved measurements of the x-ray emissions may serve as a tool for determining small level splittings in excited highly-charged ions.